2016
DOI: 10.1080/15222055.2016.1223770
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Changes in Effective Population Size during Pond Culture of Red Drum

Abstract: Reduction of genetic diversity can occur at two general phases in stock enhancement: spawning and pond culture. In the latter case, reduction in genetic diversity can take place if mortality impacts family groups disproportionately during pond culture. The stock enhancement program developed by the Texas Parks and Wildlife for Red Drum Sciaenops ocellatus was used to determine whether this phenomenon occurs with any regularity. Larvae were sampled prior to pond culture to determine the genetic effective size (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Consequently, the S. marmoratus population may have a high capacity to adapt to the environment (Xue, Zhang, Li, & Liu, ). Previous research has shown that a population with small effective population size (Ne) will cause genetic diversity to be depleted, will increase random drift and threaten the survival and evolution of the population (Anderson, Cason, & Chavez, ; Frankham, Briscoe, & Ballou, ). Unlike other marine species, such as Fenneropenaeus chinensis and Portunus trituberculatus, which have suffered too much human interference (for example, intensive catching and stock enhancement) in the northwestern Pacific (Liu et al, ; Song, Li, Zhang, & Gao, ), the S. marmoratus population has a large Ne (67.0 ‐∞), low genetic relatedness (<0.01) and a low level of inbreeding (<0.12).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the S. marmoratus population may have a high capacity to adapt to the environment (Xue, Zhang, Li, & Liu, ). Previous research has shown that a population with small effective population size (Ne) will cause genetic diversity to be depleted, will increase random drift and threaten the survival and evolution of the population (Anderson, Cason, & Chavez, ; Frankham, Briscoe, & Ballou, ). Unlike other marine species, such as Fenneropenaeus chinensis and Portunus trituberculatus, which have suffered too much human interference (for example, intensive catching and stock enhancement) in the northwestern Pacific (Liu et al, ; Song, Li, Zhang, & Gao, ), the S. marmoratus population has a large Ne (67.0 ‐∞), low genetic relatedness (<0.01) and a low level of inbreeding (<0.12).…”
Section: Discussionmentioning
confidence: 99%